Tomorrow's lawyers an introduction to your future - Susskind, Richard (Oxford University Press, 2023)
"The legal market is in a remarkable state of flux. New ways of delivering legal services are emerging, new providers are becoming firmly established in the market, and the workings of our courts are being transformed. Unless they adapt, many traditional legal businesses will fail. On the other hand, in these fluid times, a whole set of new opportunities are presenting themselves to entrepreneurial and creative young lawyers. I believe there are three main drivers of this change. I call these the 'more-for-less' challenge, liberalization, and technology. Other commentators may point to different factors, such as diversity and inclusion, shifting demography, climate change, mental health, threat of war, and globalization. I do not deny that such factors are hugely significant but my specific focus here is on the changes that we will see in the way in which legal services are delivered; and all my research and advisory work, as well as what I have seen in other professions, lead me to the conviction that, in relation to how legal work is undertaken, my three drivers are the ones to watch for. Let me introduce each in turn"--